Larvicidal and Histopathological Effects of Cassia siamea Leaf Extract against Culex quinquefasciatus - Kanitta Jiraungkoorskul; Wannee Jiraungkoorskul (Tropical Life Sciences Research, 2015)
A traditional Thai medicinal extract from Cassia siamea was evaluated with respect to its larvicidal properties by determining the median lethal concentration (LC50) at 24, 48, 72 and 96 h against the fourth instar larvae of Culex quinquefasciatus, which is a carrier of mosquito-borne diseases, by studying the histopathological alterations. The 24, 48, 72 and 96 h LC50 values were 394.29, 350.24, 319.17 and 272.42 ppm, respectively. The histopathological lesions after exposure to 25% of the 24-h LC50 were observed primarily in the midgut of the larva. Lesions with edema, swelling, and deformation or elongation of the epithelial cells were observed. Moreover, cells protruding into the lumen and absent microvilli were also found in some areas. The present study reveals that aqueous C. siamea leaf extracts have natural biopesticide properties. Suatu ekstrak ubatan tradisional Thai daripada Cassia siamea telah dinilai menggunakan sifat-sifat larvisidnya dengan menentukan kepekatan maut median (LC50) pada jam 24, 48, 72 dan 96 terhadap larva instar keempat Culex quinquefasciatus, yang merupakan pembawa jangkitan tungau, dengan mengkaji perubahan histopatologikal. Nilai LC50 pada jam 24, 48, 72 dan 96 ialah 394.29, 350.24, 319.17 and 272.42 ppm, masing-masing. Lesi histopatologikal selepas pendedahan kepada 25% daripada 24-h LC50 telah diperhatikan terutamanya diusus tengah larva. Lesi dengan edema, pembengkakan, dan pencacatan ataupun pemanjangan sel epitilial telah diperhatikan. Selain itu, sel-sel yang protrud ke dalam lumen dan ketiadaan mikrovili juga diperhatikan pada sesetengah kawasan. Kajian ini menunjukkan bahawa ekstrak akueus daun C. siamea mempunyai sifat-sifat biopestisid semulajadi.